Healthy Gardens/Healthy Lives: Navajo Perceptions of Growing Food Locally to Prevent Diabetes and Cancer. Issue 2 (March 2014) - Lombard, Kevin A.; Beresford, Shirley A. A.; Ornelas, India J.; Topaha, Carmelita; Becenti, Tonia; Thomas, Dustin; Vela, Jaime G.
Poor access to nutritious foods, departure from traditional diets, and reduced physical activity are associated with a rise in type 2 diabetes and certain types of cancers among the Navajo. Diabetes in particular is of concern because of its increased prevalence among Navajo youth. Gardening can successfully address issues of poor availability of fruits and vegetables and offer many other social and health benefits. Our assessment aimed to determine Navajo attitudes about gardening and health in San Juan County, New Mexico. We conducted seven focus groups (including 31 people) to assess knowledge and attitudes related to gardening and uncover barriers and facilitators to participation in a garden project. Each group session was moderated by two Navajo students. Transcripts revealed that many Navajo are aware of adverse health issues that occur on the reservation, predominantly obesity and diabetes. Participants expressed a preference for educational approaches that incorporated cultural traditions, respect for elders, use of visual aids, and experiential learning. Several social and agronomic barriers to gardening were also mentioned. Results suggested a broad interest in promoting gardening especially to reduce the risk of diabetes with the added value of enhancing social capital in Navajo communities.